Taxonomic review of the monotypic genus Dinahia Bechyně, 1946 (Coleoptera: Chrysomelidae: Chrysomelinae) - Sampaio, Aline; Fonseca, Claudio Ruy Vasconcelos Da (Zootaxa, 2024)
The monotypic genus Dinahia Bechyně, 1946, endemic to the Atlantic Forest (Rio Grande do Sul, Santa Catarina, and São Paulo), is reviewed. Dinahia privigna Bechyně, 1946 is redescribed, and, for the first time, the aedeagus and spermatheca of this species are described and illustrated herein. Additionally, a diagnosis for the genus, a nomenclatural history, photographs of both non–type specimens and the syntype, a geographic distribution map, and a discussion of Dinahia and similar genera according to the bibliography (Calligrapha Chevrolat, 1836; Cosmogramma Erichson, 1847; Desmogramma Erichson, 1847; Grammomades Achard, 1923; and Zygogramma Chevrolat, 1836) are provided. This discussion incorporates a comparative table encompassing characters extracted from the antennae, maxillary palps, prosternal, mesoventral, and metaventral processes, V tarsomeres, and claws. Additionally, it includes an illustrated replacement couplet for step 22 in Sampaio & Fonseca’s (2023) identification key, both to elucidate Dinahia’s differentiations and similarities from these five genera.